2001
DOI: 10.1046/j.0022-202x.2001.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor and 1α,25-Dihydroxyvitamin D3 Suppress Lipogenesis in Hamster Sebaceous Gland Cells In Vitro

Abstract: We have previously reported the establishment of a culture system of hamster auricular sebocytes. Although their morphologic and biochemical properties are very similar to those of human sebocytes, the regulation of lipogenesis is not clear. Therefore, we investigated the effect of epidermal growth factor, all-trans retinoic acid, 1alpha,25-dihydroxyvitamin D3, and androgens such as testosterone and 5alpha-dihydrotestosterone on lipogenesis in cultured hamster sebocytes. Intracellular lipid droplets detected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 36 publications
2
60
0
3
Order By: Relevance
“…표피성장인자는 지방형성을 억제하여 세포 내 중성 지방 농도를 낮춘다고 알려져 있으며, 재조합 인간 표 피성장인자를 도포할 경우, 여드름양 발진이 임상적으 로 호전되고, 여드름에 도포할 경우 피지분비량이 감 소하고, 피부 수분량이 증가한다고 알려져 있다 [5][6][7]. 이전 연구들을 통해 표피성장인자 외용제가 피지분비 조절 및 여드름 병변을 호전시킬 것으로 예상되는 바, 본 연구에서는 표피성장인자를 함유한 외용제의 효과 와 안전성을 평가하고자 하였다.…”
Section: 서 론unclassified
“…표피성장인자는 지방형성을 억제하여 세포 내 중성 지방 농도를 낮춘다고 알려져 있으며, 재조합 인간 표 피성장인자를 도포할 경우, 여드름양 발진이 임상적으 로 호전되고, 여드름에 도포할 경우 피지분비량이 감 소하고, 피부 수분량이 증가한다고 알려져 있다 [5][6][7]. 이전 연구들을 통해 표피성장인자 외용제가 피지분비 조절 및 여드름 병변을 호전시킬 것으로 예상되는 바, 본 연구에서는 표피성장인자를 함유한 외용제의 효과 와 안전성을 평가하고자 하였다.…”
Section: 서 론unclassified
“…Since hamster sebocytes constitutively produce TGs during cultivation in vitro [32], we first examined the effect of β-CRX on constitutive TG production in cultured hamster sebocytes. As shown in Figure 2(A), β-CRX was found to decrease the level of TGs in a dose-dependent manner (70% inhibition at 10 μM).…”
Section: Inhibition Of Tg Production and Dgat-1 Gene Expression By β-mentioning
confidence: 99%
“…Hamster sebocytes (2.4 × 10 4 cells/cm 2 ) [32] were plated onto 96-well multiplates, 35-mm or 100-mm diameter culture dishes (Becton Dickinson, Tokyo, Japan) and then cultured for 24 h in DMEM/F12 (Invitrogen, Carlsbad, CA) supplemented with 6% heat-denatured fetal bovine serum (Nichirei Biosciences Inc., Tokyo, Japan), 2% human serum (C-C Biotech Co., Valley Center, CA), 0.68 mM L-glutamine (Invitrogen), and recombinant human epidermal growth factor (10 nM) (Progen Biotechnik GmbH, Heidelberg, Germany) to achieve complete cell adhesion as previously described [6,18]. The hamster sebocytes were treated every two days for up to 8 days with or without β-CRX (purity ≥ 95%; Shikoku Yashima Pure Chemicals, Tokushima, Japan) (Figure 1) or 13-cisRA (Sigma Chemical, St. Louis, MO) in the presence or absence of a sebocyte-differentiation inducer, insulin (10 nM) (Sigma Chemical) [12] in DMEM/F12 supplemented with heat-denatured fetal bovine serum, human serum, and L-glutamine.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…The secretion of triglycerides in human colon adenocarcinoma Caco-2 cells was stimulated by EGF (11). However, EGF decreased the intracellular accumulation of triglycerides in hamster auricular sebocytes (12). The stimulation of triacyl glycerol synthesis by insulin in primary cultures of adult rat hepatocytes was also suppressed by EGF through the inhibition of malic enzyme activity (13).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that EGF regulated the secretion and formation of lipids in various cells (11)(12)(13). The secretion of triglycerides in human colon adenocarcinoma Caco-2 cells was stimulated by EGF (11).…”
Section: Introductionmentioning
confidence: 99%